The Application Of The Problem Based Learning (PBL) Model To Improve Student Learning Outcomes In Islamic Religious Education Subjects In The Beautiful Material Of Mutual Respect For The Elements Of Akhlaq Phase C Class V At SDIT Plus Al-Muhsinin, Cangkuang District - Romadhoni, Irfan Rofiq Hamdan; Basyari, Achmad Muharam; Hidayat, Syarif (UMSU, 2025)
This study aims to provide an overview of the effectiveness of implementing the Problem-Based Learning (PBL) model in promoting student learning outcomes, particularly in Islamic Religious Education and Moral Education subjects. The study was conducted as a Classroom Action Research (CAR) consisting of two cycles and implemented in class V-B of SDIT Plus Al-Muhsinin, Cangkuang District, Bandung Regency, during the 2024/2025 academic year. The number of students participating in the study was 17. Data collection techniques included observation, documentation, formative tests, and interviews, which were then analyzed using a quantitative and qualitative descriptive approach. Findings from the first cycle indicated that student learning outcomes were still relatively low, with an average score of 67 and a classical completion rate of only 52.94%. Thus, it can be concluded that the PBL model has been proven and can be recommended as an innovative and relevant alternative learning approach to be integrated into educational practices at the elementary school level, particularly by emphasizing teachers as key facilitators in implementing systematic patterns and providing motivational encouragement to students.